Investigating EFL Students’ Perceptions on E-learning Paradigm-Shift During Covid-19 Pandemic - Rahim, Mohammad Naim; Chandran, Shanti Sandaran Chandran (Universitas Lancang Kuning, 2021)
The purpose of this research article is to investigate the perceptions of EFL students during the Covid-19 pandemic on implementing e-learning at university-level education in the EFL context of Afghanistan. The covid-19 pandemic has globally led the universities towards a paradigm-shift. As well as the instant development of ICT has restructured the content and the context of education particularly teaching and learning EFL. To determine the barriers and opportunities of implementing e-learning in EFL education, a qualitative method with semi-structured interview are applied to perceive the perceptions of EFL students. The study purposefully selected EFL students (N= 21 male and female) from Afghanistan universities as respondents. The data from the semi-structured interview is analyzed thematically. Results show that EFL students perceive e-learning approach as a better alternative to traditional face-to-face classrooms. Despite being regarded as an interactive method for EFL education, the lack of regular electricity connection, low internet bandwidth, high costs of ICT tools, lack of infrastructures, and lack of ICT knowledge of the teachers and students are perceived to be the barriers to implementing e-learning in Afghanistan higher education. In brief, the study contributes to establishing an in-depth understanding of the e-learning implementation and EFL instructions in Afghanistan higher education during the Covid-19 pandemic.